Contribution of limbs’ actions to the four competitive swimming strokes: a nonlinear approach - Bartolomeu, Raúl Filipe (2018)
The aim of our study was to assess the effect of the limbs’ actions on the nonlinear properties of the four competitive swimming strokes. Forty-nine swimmers performed all-out sprints at front-crawl, backstroke, breaststroke and butterfly, each one at full stroke (FS), only the arms’ stroke (AS), and only leg kicking (LK), in a total of 12 bouts, 6 per day. A speedo-meter cable was attached to the swimmer’s hip, to collect the speed-time raw data (f = 50Hz). Velocity, speed fluctuation, sample entropy and fractal dimension were derived from the speed-time series. Significant and moderate-strong effects were noted for both stroke and condition in all variables in the study (p ≤ 0.001; 0,560<η2 < 0,952). The four competitive strokes and their three conditions exhibited nonlinear properties. The swimming pattern was less complex and more predictable for LK in comparison to AS and FS. Breaststroke and butterfly have more complex but more predictable patterns than backstroke and front-crawl.